A call for increased public engagement in geology higher education. (18th March 2013) - Robb, Jane
<x xml:space="preserve">Abstract</x> Rising fees are forcing higher education institutions to think critically about what students are offered for their money. In geology courses there appears to be a lack of guidance for alternative careers in academia or industry, and even a lack of education about wider social, political and economic impacts of the discipline. It is possible to detect a lack of high‐impact geoscience among the popular science communication communities, such as online multidisciplinary blogging platforms. In order to enhance the student experience and the impact of geoscience on the wider public, universities need to look inwards at what they can do to help inspire and educate students to have broader career horizons and bigger public impacts through their research.